Synthesis of LaNiO3 perovskite by the proteic gel modified method using collagen - Santos, J. C.; Souza, M. J. B.; Mesquita, M. E.; Pedrosa, A. M. G. (Scientia Plena, 2012)
The perovskite oxides are strategic materials due its catalytic, electronic and magnetic properties. These properties are influenced by the calcinations and synthesis conditions. This work describes a study on the synthesis of LaNiO3 perovskites via modified proteic gel method varying the content of collagen. Perovskites oxides with the composition LaNiO3 were synthesized by modified proteic gel method using nickel nitrate, lanthanum nitrate and collagen as starting source. The obtained powders were characterized by thermogravimetric analysis (TGA), infrared spectroscopy (FTIR) and X-ray diffraction. TGA curves and FTIR spectra were particularly useful in establishing of the optimal calcination temperature of the precursor powders. X-ray diffraction patterns revealed the formation of the perovskite structure in all samples prepared by synthesis method varying the content of collagen and after calcinations at 700 °C four 2 hours. In the optimization of the collagen content, the bester bulk proportion of metal (Ni2+)/collagen used was 1.0:1.0, where it was possible to obtain monophasic perovskite.